The lived experiences of claiming wrongful conviction in prison - Burtt, Emma (Routledge frontiers of criminal justice, 2024)
The Lived Experiences of Claiming Wrongful Conviction in Prison focuses on the lived experience of maintaining innocence in the prison environment and highlights the struggles and pain that such a claim can cause